2
$\begingroup$

Let X be a random variable following normal distribution with mean +1 and variance 4. Let Y be another normal variable with mean -1 and variance unknown. If $$P(X\leq-1)=P(Y\geq2)$$ then standard deviation of Y is

My Solution:

$E(X)=\mu=1, V(X)=\sigma^2=4$ as

$\sigma^2=E[X^2]-(E[X])^2=E[X^2]-\mu^2$

$4=E[X^2]-1^2$

$\implies E[X^2]=5$

Now How can we calculate $\sigma^2$ for Y

$\endgroup$
  • $\begingroup$ Your "solution" does not use the given equality. So - as to be expected - is not fruitful. $\endgroup$ – drhab Jan 23 '15 at 12:22
1
$\begingroup$

We will use the fact that $P(Z\le-1)=P(Z\ge1)$, where $Z$ is a standard normal random variable. We have that $$ P(X\le-1)=P\biggl(\frac{X-1}2\le-1\biggr), $$ $$ P(Y\ge2)=P\biggl(\frac{Y+1}\sigma\ge\frac3\sigma\biggr) $$ and $$ P\biggl(\frac{X-1}2\le-1\biggr)=P\biggl(\frac{Y+1}\sigma\ge\frac3\sigma\biggr). $$ $(X-1)/2$ and $(Y+1)/\sigma$ are both standard normal random variables. Hence, $3/\sigma$ must be equal to $1$ and $\sigma$ to $3$.

$\endgroup$
0
$\begingroup$

The random variables $X$ and $Y$ can be written as $X=2U+1$ and $Y=\sigma V-1$ where $U$ and $V$ both have standard normal distribution.

$P\{U\geq 1\}=P\{U\leq -1\}=P\{X\leq -1\}=P\{Y\geq2\}=P\{V\geq\frac{3}\sigma\}=P\{U\geq\frac{3}\sigma\}$

The first equality is a consequence of the fact that the standard normal distribution is symmetric. The last equality is a consequence of the fact that $U$ and $V$ have the same distribution.

So $1=\frac{3}\sigma$, so that $\sigma^2=9$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.